Politik Hukum Pembentukan Norma Pada Perubahan Regulasi Masa Jabatan Kepala Desa - Khozin, Ahmad Nur; Diniyanto, Ayon (Manabia: Journal of Constitutional Law, 2025)
The demonstration by the village head association demanding an extension of office resulted in changes in Law Number 3 of 2024 which contains the norm for the term of office of village heads into 2 periods with each term of office for 8 years. This change does not show a significant difference with the previous regulation, in fact it experiences regulatory similarities with Law Number 5 of 1979 during the new order period. This research aims to find out the legal politics of changes in the term of office norms of village heads and explain the legal consequences. By using a legal approach, a conceptual approach, and a historical approach. The author uses perscriptive analysis techniques in reviewing the research. With the result that; First, even though the making of laws seems hasty, the legal politics used in making this policy lead to public welfare. Second, the legal consequences arising from changes in the norms of the term of office of the village head. Keywords: Village Law; Village head; Legal Politics